Design and development of pH-responsive levofloxacin-loaded metal-organic framework for the promising treatment of pediatric abdominal wound repair - Guoyan Wang; Hongwei Li; Xinhua Shao; Shuisheng Teng; Qiong Wu (Regenerative Therapy)
With over 9 million fatalities per year expected by 2030, infectious diseases will remain a significant burden on the world economy and cause high mortality rates. An excellent method to increase the bioactivity of levofloxacin (LEV) in pediatric abdominal wound repair is the finding of a stimuli-based drug delivery system (DDS). We designed and developed an LEV incorporated with zeolite imidazole framework-8 (ZIF-8) as a promising nanocarrier for wound healing applications. The spectral analysis and morphological analysis confirm the formation of our newly fabricated composites. Mouse embryonic fibroblast NIH3T3 cells, the cytotoxicity, cytocompatibility, and cell proliferation characteristics of LEV@ZIF-8 were evaluated in vitro. LEV@ZIF-8 composite considerably improved the biocompatibility against NIH3T3 cells after 72-h of exposure, according to in vitro experiments. Under acidic circumstances, the pH-responsive drug release studies exhibit superior LEV release, and in physiological circumstances, there is no unintended drug release. The LEV@ZIF-8 composite-treated cells demonstrate the most remarkable cell growth and migration method in a very short time, according to the results of the wound scratch experiment. The composite exposure concentration depended on inhibition against various microorganisms in the antibacterial activity testing. According to the study, LEV@ZIF-8 are appropriate and effective DDS for stimuli-based pediatric abdominal wound repair.